2021
DOI: 10.1111/ggi.14170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinical pharmacists' interventions on dementia treatment adherence and caregivers' knowledge

Abstract: The aim of this study was to evaluate the effect of clinical pharmacists' interventions on the adherence to dementia treatment and the caregivers' knowledge of dementia.Methods: This study was conducted at a geriatric outpatient clinic of the university hospital between October 2018 and April 2019. The Morisky Green Levine Adherence Scale (MGLS) to patients or caregivers and the Dementia Knowledge Assessment Tool Version Two (DKAT2) to caregivers were applied at the beginning of the study and 4 months later by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Overall, the results showed that 71% of the patients presented satisfactory treatment adherence, which is similar to other studies which measured adherence also through the patient's caregiver ( 27 , 28 ). In a multicenter, cross-sectional, observational study ( 27 ) found a 63% treatment adherence, although they evaluated the degree of adherence to transdermal vs .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the results showed that 71% of the patients presented satisfactory treatment adherence, which is similar to other studies which measured adherence also through the patient's caregiver ( 27 , 28 ). In a multicenter, cross-sectional, observational study ( 27 ) found a 63% treatment adherence, although they evaluated the degree of adherence to transdermal vs .…”
Section: Discussionsupporting
confidence: 87%
“…oral formulation of rivastigmine, a different study goal from the current study but with similar values of adherence. Another similar study ( 28 ) observed a 70.2% degree of adherence to dementia drugs before and after a pharmaceutical intervention at a geriatric outpatient clinic of the university hospital.…”
Section: Discussionmentioning
confidence: 74%
“…Factors affecting persistence and adherence include severity of dementia, education level, drug burden, economic status, and adverse drug reactions 11,13,18–24 . Whether different AD drugs affect treatment persistence or adherence varied among studies 12,25–27 . Caregiver support and knowledge of disease and medications are crucial for treatment adherence and efficacy 27–29 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Initially, it has been validated on 290 hypertensive patients showing an adequate reliability and internal consistency (Cronbach alpha = 0.61). It has been later used for the detection of nonadherence in other several health conditions in both Arabic-and non-Arabic speaking contexts [5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: The Morisky Green and Levine (Mgl) Medication Adherence Scalementioning
confidence: 99%
“…While the other adherence scales developed by Prof. Morisky are copyrighted, the MGL scale is in the public domain and has been largely cited in the last decade in several research studies, including studies from the MENA region and Jordan [5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%